Steroid Cell Tumor of Ovary Not Otherwise Specified in A Child - Ramraje, Sushma Nagsen; Pirosha, Arva Ali; Matthew, Neha (Annals of Pathology and Laboratory Medicine, 2020)
Steroid cell tumour of the ovary is a very rare sex cord stromal tumour of ovary which commonly presents in women belonging to third and fourth decade of life. It usually manifests with a pelvic mass along with androgenic symptoms. We present a case of 3 year old child, who presented with precocious puberty and hirsutism. Radiology was suggestive of ovarian mass for which oophorectomy was done. Gross, histopathological examination and immunohistochemistry proved it to be a steroid cell tumour, not otherwise specified. Our case being unique because of presentation at merely 3 years of age.